Spiral Lyrical Composition - Nikishov, Yurii (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
In the paper, spiral lyrical composition is described for the first time. Usually a poet’s description or reflection is performed from a fixed point of view. The originality of a spiral lyrical composition consists in the fact that along with the movement of the description or reflection, the point of view moves as well. Poems of Aleksandr Blok and Aleksei Yerantsev are considered as examples of spiral composition.